Investigation of polymeric biodegradable-biocompatible Janus particles in drug delivery systems and further augmentation via a facile synthesis method - Lim, Jerome Yi Guang (Nanyang Technological University, 2020)
Janus particles have been garnering considerable interest in recent times. Traditionally, Janus particles have been fabricated via Pickering Emulsions and Sputtering processes. Due to the harsh nature of these processes, the types of materials that could be used for Janus particles were primarily inorganic or metallic in nature. Polymeric Janus particles were generally not suitable for such methods due to the high temperatures and solvents used in these processes. To fabricate polymeric Janus particles, the predominant method had been microfluidics via co-jetting. Due to the extra care needed in the co-jetting process, this method usually suffers from extremely low throughputs. A breakthrough study in 2012 demonstrated the fabrication of polymeric poly(lactic-co-glycolic) acid (PLGA)/poly (caprolactone) (PCL) Janus particles via a solvent emulsion method, which could potentially circumvent the issue of low throughputs in microfluidics. However, various intrinsic issues such as the loss of Janus morphology upon drug addition had caused a halt in this research area. The work shown in this thesis attempts to address the issue of drug addition to polymeric biodegradable/biocompatible Janus particles via the solvent emulsion method. By understanding the thermodynamics behind the formation of Janus particles via the solvent emulsion method, various achievements such as dual-drug encapsulation, selective encapsulation of drugs and diagnostic materials can be carried out in a single-step synthesis. As will be discussed in detail of this thesis, the spontaneous and automatic partitioning behavior of drugs and diagnostic agents is found to be driven by thermodynamic factors, without requiring external intervention. Additionally, unique drug-release behavior depending on polymer combination is also demonstrated as a result of this selective encapsulation behavior. Various applications such as potential treatments to diabetes based on utilizing the selective encapsulation of drugs and diagnostic materials are also shown in a proof-of-concept model. Other additional derivatives such as Janus superstructure fabrication was also shown possible within this single-step synthesis method through the understanding of the formation mechanics of Janus particles.